2018
DOI: 10.1186/s12879-018-3488-8
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus and Epstein-Barr virus infections, risk factors, and their influence on the liver function of patients with acute-on-chronic liver failure

Abstract: BackgroundStudies on human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV) have focused primarily on the immunosuppressed population. Few studies have considered immunocompetent and not severely immunocompromised patients. We determined the infection rates of HCMV and EBV, their risk factors and their influence on liver function in patients with HBV-related acute-on-chronic liver failure (ACLF).MethodsPatients infected with ACLF-based hepatitis B virus (HBV) from 1 December 2016 to 31 May 2018 were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
10
1
3
Order By: Relevance
“…La infección primaria por este virus suele ser adquirida durante la infancia; posteriormente establece un periodo de persistencia a través de las células mieloides o granulocíticos. (5,6) La reactivación o reinfección por virus exógenos es posible y causa alta mortalidad en pacientes inmunocomprometidos, como los que padecen algún tipo inmunodeficiencias o pacientes transplantados. (5,7) El VEB es un virus herpes de clase γ.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La infección primaria por este virus suele ser adquirida durante la infancia; posteriormente establece un periodo de persistencia a través de las células mieloides o granulocíticos. (5,6) La reactivación o reinfección por virus exógenos es posible y causa alta mortalidad en pacientes inmunocomprometidos, como los que padecen algún tipo inmunodeficiencias o pacientes transplantados. (5,7) El VEB es un virus herpes de clase γ.…”
Section: Discussionunclassified
“…(5,6) La reactivación o reinfección por virus exógenos es posible y causa alta mortalidad en pacientes inmunocomprometidos, como los que padecen algún tipo inmunodeficiencias o pacientes transplantados. (5,7) El VEB es un virus herpes de clase γ. La infección primaria suele manifestarse con un cuadro de mononucleosis infecciosa, caracterizado por fiebre, faringitis y linfadenopatía cervical con o sin hepatoesplenomegalia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…According to the manufacturer’s instructions, EBV DNA was extracted from blood samples using DNA extraction kit (Daan Gene Co.Ltd., Zhongshan University, China). Quantitative polymerase chain reaction (PCR) was detected on a real-time PCR system (Stratagene MX3000P; Agilent Technologies, Santa Clara, CA, USA), just as our previous reported [30].…”
Section: Methodsmentioning
confidence: 99%
“…While numerous studies have reported CMV in patients undergoing organ transplantation or HSCT, few studies are available regarding CMV infection in patients with liver failure ( Cho et al., 2019 ). A retrospective study conducted in China analyzed the risk factors for both CMV and Epstein-Barr virus infection and their influence on the liver function of patients with ACLF-based hepatitis B virus, indicating that 5% (5/98) of the patients presented with CMV DNA ( Hu et al., 2018 ). However, the study was conducted on a small scale, and the influence of prognosis on CMV infection was not confirmed.…”
Section: Introductionmentioning
confidence: 99%